ANALISIS FIXED EFFECT MODEL LUAS PANEN DAN PRODUKSI PADI TERHADAP PDRB PADA 5 PROVINSI DI INDONESIA - Cut Putri Mellita Sari; Noviami Trisniarti (LPPM Universitas Malikussaleh - Indonesia, 2023)
This study aims to examine the effect of Rice Harvest and Production Area on Gross Regional Domestic Product (GDP). The phenomenon that occurs that when the area of harvest and production decreases but GDP shows an increase, further studies are needed regarding the effect of broad harvest and rice production on GDP. The samples in this study are 5 provinces in Indonesia and have the largest rice production, namely West Java, Central Java, East Java, South Sulawesi and South Sumatra in 2018-2022. In this study, the data was processed using Eviews with panel data regression analysis. From the Chow test and Hausman test, the Fixed Effect Model (FEM) model was selected as the best estimation model. The results showed that the area of rice harvest and production together affect the GRDP in 5 provinces in Indonesia. Meanwhile, partially, the harvest area has a negative effect on GDP while rice production has no effect on GDP in 5 provinces in Indonesia during the period 2018-2022. It is recommended that the government further improve the farmer insurance program and farmer group training so as to further increase GDP